Sustainability and automation in smart constructions : proceedings of the International Conference on Automation Innovation in Construction (CIAC-2019), Leiria, Portugal /: proceedings of the International Conference on Automation Innovation in Construction (CIAC-2019), Leiria, Portugal. ([2021]) - Unknown
No abstract available